Armenia as a Digital Bridge Gate: Innovation and communication pathways with the Global South - Armen Ghazaryan; Anna Kirakosyan (OrdnungsPolitisches Portal (OPO), 2025)
Armenia, strategically positioned at the geopolitical crossroads of East and West, is actively pursuing a transformative agenda to establish itself as a "Digital Bridge Gate." This article examines Armenia's digital infrastructure and burgeoning innovation capabilities, analyzing their potential to foster robust communication and trade pathways with the Global South. Leveraging quantitative metrics from the Network Readiness Index (NRI) 2024, the analysis benchmarks Armenia's performance in ICT development, internet penetration, e-government, and digital trade capacity against key Global South nations and developed economies. The report identifies Armenia's existing digital diplomacy initiatives, such as its cooperation with India on Digital Public Infrastructure and its economic partnership with the UAE. It argues that Armenia's unique blend of advanced human capital in software development and a supportive regulatory environment positions it not merely as a conduit but as a potential "Digital Hub" for South-South digital collaboration. Policy recommendations focus on accelerating infrastructure upgrades, boosting AI research, enhancing digital literacy, and strategically leveraging its digital expertise to deepen ties with the Global South, thereby reinforcing its geopolitical resilience and economic diversification.
Keywords: 330; Digital Gateway-Bridge; Global South; Digital Infrastructure; Innovation; Digital Diplomacy; Armenia